Indonesia’s political culture in the new digital age: A preliminary discussion - Ari Ganjar Herdiansah; Widya Setiabudi Sumadinata (Faculty of Social and Political Science, Universitas Airlangga, 2019)
The development of increasingly accessible digital media has resulted in reasonably intense dynamics of political behaviour and articulation. However, the influence of the internet and social media use on Indonesian political culture has not been much discussed. This article explains changes in contemporary Indonesia’s political culture that align with the proliferation of new digital media by considering socio-political conditions and modernization. In its analysis, this article employs a historical-comparative method with an interpretive approach. The results of this study demonstrate that the traditional conception of power relation has historically influenced Indonesian political culture. In the post-Suharto era, the direct electoral system and primacy of television media promoted popular voter preferences that degraded traditional charismatic figures. The rise of the Internet and social media then had democratizing implications by increasing online public discussion. However, subsequent development of new digital media also illustrated counterproductive trajectory to democratic values as online frictions triggered ethnic and religious-based regrouping. Finally, this article considers that although widespread usage of the Internet and social media inspire democratic implications to Indonesian political culture, longstanding and deep-rooted traits, such as primordialism, persist within this more digitalized society.